Copper excess induces autophagy dysfunction and mitochondrial ROS-ferroptosis progression, inhibits cellular biosynthesis of milk protein and lipid in bovine mammary epithelial cells - Ya Ting Fan; Dong Qiao Peng; Jing Lin Shen; Jun Hao Cui; Xin Yue Yang; Jin Ge Zhang; Yong Cheng Jin (Ecotoxicology and Environmental Safety)
Excessive copper (Cu) has the potential risk to ecosystems and organism health, with its impact on dairy cow mammary glands being not well-defined. This study used a bovine mammary epithelial cell (MAC-T) model to explore how copper excess affects cellular oxidative stress, autophagy, ferroptosis, and protein and lipid biosynthesis in milk. Results showed the increased intracellular ROS, MDA, and CAT (P < 0.05), alongside decreased T-SOD and GSH in CuSO4-treated cells (P < 0.05). Transmission electron microscopy and Ad-mCherry-GFP-LC3B assays revealed significant autophagosome accumulation in CuSO4 exposed cells (P < 0.05). Additionally, CuSO4 exposure modulated autophagy markers, evidenced by upregulation of genes such as LC3, ATG5, JNK1, and Beclin1, and downregulation of genes such as ATG4B, and p62 (P < 0.05). CuSO4 also led to notable mitochondrial changes, including size reduction, membrane rupture, and cristae loss, and reduced expression of the ferroptosis inhibitor GPX4 (P < 0.05). The expression of mTOR, HIF-1α and β-catenin signaling pathway were inhibited in differentiated MAC-T cells by CuSO4 exposure (P < 0.05), activated autophagy through activation of the AMPK-mTOR pathway which in turn affected downstream levels of genes related to milk protein and lipid. In conclusion, excessive copper induces oxidative stress in MAC-T cells, promoting autophagy through JNK-Bcl2, Beclin1-Vps34 and AMPK-mTOR pathways, leading to cell ferroptosis, as well as inhibits the cellular biosynthesis of milk protein and lipid.